OPTIMALISASI PEMBUATAN HAND SANITIZER BERBASIS GEL LIDAH BUAYA DI DESA WANAMULYA, KABUPATEN PEMALANG - Wisnu Broto; Fahmi Arifan; Edy Supriyo; nanik kartikasari; Oktaviani Kusuma Wardani; Mirza Muhammad Faisal (Sekolah Vokasi Universitas Diponegoro, 2022)
Wanamulya Village is one of 13 villages in Pemalang District, Pemalang Regency. Wanamulya Village has an area of 495,375 Ha. To the west it is bordered by Tambakrejo Village, to the north by Bojongnangka Village, to the south by Banjarmulya Village, to the east by Mengori Village. The condition of the village land is dominated by rice fields. The aloe vera plant which was previously underutilized can now be converted into an addition to the manufacture of hand sanitizers so that people no longer buy hand sanitizers in the market. Hand sanitizer is easy to make independently of a mixture of alcohol and water. Alcohol with a high concentration will kill the virus, but at the same time cause the skin to become dry with high frequency of use. To reduce this, additive compounds are needed, one of which is aloe vera as a softener and antibacterial because it contains aloe vera. The purpose of this community service is to educate the public in making hand sanitizers by adding additives in the form of aloe vera. The results of this community service activity have an impact on public knowledge about making hand sanitizers with the addition of aloe vera independently, which is very visible from the enthusiasm of the people of Wanamulya Village in participating in this service program.